Surgical Options for Failed Rotator Cuff Repair, except Arthroplasty: Review of Current Methods - Jangwoo Kim; Yunki Ryu; Sae Hoon Kim (Clinics in Shoulder and Elbow, 2020)
Although the prevalence of rotator cuff tears is dependent on the size, 11% to 94% of patients experience retear or healing failure after rotator cuff repair. Treatment of patients with failed rotator cuff repair ranges widely, from conservative treatment to arthroplasty. This review article attempts to summarize the most recent and relevant surgical options for failed rotator cuff repair patients, and the outcomes of each treatment, except arthroplasty.